Treadmill walking economy is not affected by body fat and body mass index in adults - Wesley J. Tucker; Brandon J. Sawyer; Dharini M. Bhammar; Emma W. Ware; Siddhartha S. Angadi; Glenn A. Gaesser (Physiological Reports, 2024)
Abstract To determine whether body fat and body mass index (BMI) affect the energy cost of walking (Cw; J/kg/m), ventilation, and gas exchange data from 205 adults (115 females; percent body fat range = 3.0%–52.8%; BMI range = 17.5–43.2 kg/m2) were obtained at rest and during treadmill walking at 1.34 m/s to calculate gross and net Cw. Linear regression was used to assess relationships between body composition indices, Cw, and standing metabolic rate (SMR). Unpaired t‐tests were used to assess differences between sex, and one‐way ANOVA was used to assess differences by BMI categories: normal weight, <25.0 kg/m2; overweight, 25.0–29.9 km/m2; and obese, ≥30 kg/m2. Net Cw was not related to body fat percent, fat mass, or BMI (all R2 ≤ 0.011). Furthermore, mean net Cw was similar by sex (male: 2.19 ± 0.30 J/kg/m; female: 2.24 ± 0.37 J/kg/m, p = 0.35) and across BMI categories (normal weight: 2.23 ± 0.36 J/kg/m; overweight: 2.18 ± 0.33 J/kg/m; obese: 2.26 ± 0.31, p = 0.54). Gross Cw and SMR were inversely associated with percent body fat, fat mass, and BMI (all R2 between 0.033 and 0.270; all p ≤ 0.008). In conclusion, Net Cw is not influenced by body fat percentage, total body fat, and BMI and does not differ by sex.